On a Class of Combinatorial Sums Involving Generalized Factorials - W.-S. Chou; L. C. Hsu; P. J.-S. Shiue (International Journal of Mathematics and Mathematical Sciences)
The object of this paper is to show that generalized Stirling numbers can be effectively used to evaluate a class of combinatorial sums involving generalized factorials.